1990
DOI: 10.1111/j.1460-9568.1990.tb00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Striatal NPY‐Containing Neurons Receive GABAergic Afferents and may also Contain GABA: An Electron Microscopic Study in the Rat

Abstract: Dual labelling methods were applied to localize simultaneously neuropeptide Y (NPY) and glutamate decarboxylase (GAD) immunoreactivities on ultrathin sections of the rat caudate-putamen (CP). By means of a double peroxidase-anti-peroxidase technique, using 3,3'-diaminobenzidine and benzidine dihydrochloride as chromogens in animals with no colchicine pretreatment, GAD immunoreactivity was found to be present in terminals only whereas NPY immunoreactivity was detected in neurons displaying the features of aspin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

1992
1992
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
1
10
2
Order By: Relevance
“…Nevertheless, our data are comparable to the minor diameters of Dimova's medium aspiny class IV (Dimova et al, 1980) and somatostatin-containing cells of the cat dorsal striatum . Rare, spine-like protrusions on some dendrites (DiFiglia and Aronin, 1982;Vuillet et al, 1989bVuillet et al, , 1990Gracy and Pickel, 1997;Morello et al, 1997) did not broaden out or display spine apparatus, which may explain why spines are not always reported (Takagi et al, 1983;Pickel, 1988, 1989;Massari et al, 1988;Fujiyama and Masuko, 1996). Axons immunopositive for NOS were unmyelinated and their boutons did not contain dense core vesicles, unlike previous reports in the striatal NPY/somatostatin population Fig.…”
Section: Morphology Of Nos-ir Neuronscontrasting
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, our data are comparable to the minor diameters of Dimova's medium aspiny class IV (Dimova et al, 1980) and somatostatin-containing cells of the cat dorsal striatum . Rare, spine-like protrusions on some dendrites (DiFiglia and Aronin, 1982;Vuillet et al, 1989bVuillet et al, , 1990Gracy and Pickel, 1997;Morello et al, 1997) did not broaden out or display spine apparatus, which may explain why spines are not always reported (Takagi et al, 1983;Pickel, 1988, 1989;Massari et al, 1988;Fujiyama and Masuko, 1996). Axons immunopositive for NOS were unmyelinated and their boutons did not contain dense core vesicles, unlike previous reports in the striatal NPY/somatostatin population Fig.…”
Section: Morphology Of Nos-ir Neuronscontrasting
confidence: 75%
“…There is also some question as to whether, in addition to releasing neuroactive compounds such as NPY (Wahlestedt and Hakanson, 1986;Walker et al, 1988), somatostatin (McCann, 1982), or NO (Bredt et al, 1990;Garthwaite, 1991;Manzoni et al, 1992), all neurons in this subpopulation are GABAergic. Despite the fact that not all NPY-stained neurons expressed GABA (Aoki and Pickel, 1989), all were reported to contain glutamate decarboxylase (GAD) (Vuillet et al, 1990), and, although neurons resembling the NOS-containing morphologic subtype are not reported in GAD- (Kita and Kitai, 1988) or GABA- immunolabeling studies, GABA immunoreactivity has been reported in terminals of somatostatin/NOS-positive cells (unpublished observation cited in Kawaguchi et al, 1995). Furthermore, GAD immunoreactivity and NOS immunoreactivity colocalize in colchicine-treated rats (Kubota et al, 1993).…”
Section: Morphology Of Nos-ir Neuronsmentioning
confidence: 91%
“…It may be that these two major types of interneurons (ChAT and NPY) contain other types of GABA A receptor subunits that were not investigated in this study. Previous ultrastructural studies on NPY/ somatostatin neurons have shown that, although there are only infrequent synaptic contacts on these neurons (DiFiglia and Aronin, 1982), some of these axon terminals have been shown to be GABA-positive (Aoki and Pickel, 1989;Vuillet et al, 1990); this would suggest that GABA may act on these interneurons through GABA A receptors that do not include ␣ 1 , ␣ 2 , ␣ 3 , ␤ 2,3 , and ␥ 2 subunits and/or GABA B receptors. The ChAT neurons on the other hand have been shown to have a large number of different types of synaptic contacts (Phelps et al, 1985;DiFiglia and Carey, 1986); these include GABAergic boutons (Bolam and Bennett, 1995) and substance P-and Enk-immunoreactive synaptic contacts (Bolam et al, 1986;Martone et al, 1994) that colocalise with GABA (Aronin et al, 1984;Penny et al, 1986;Besson et al, 1990).…”
Section: Cellular Distribution Of Gaba a Receptor Subunits In The Strmentioning
confidence: 95%
“…Previous studies in the rat have shown that virtually all of the striatal projection neurons are GABAergic medium-sized spiny neurons that project to the globus pallidus and substantia nigra; these GABAergic projection neurons contain the calcium binding protein calbindin (Calb), and the axons of these neurons additionally provide local axon collateral terminals within the striatum (Preston et al, 1980;Wilson and Groves, 1980;Nitsch and Riesenberg, 1988;DiFiglia et al, 1989). Various types of GABAergic interneurons have also been identified in the caudate-putamen (Bolam and Bennett 1995;Kawaguchi et al, 1995); they include a variety of types of aspiny interneurons that contain the calcium binding protein parvalbumin (Parv; Cowan et al, 1990;Kita et al, 1990;Coté et al, 1991), the calcium binding protein calretinin (Calr; Bennett and Bolam 1993;Bennett and Bolam 1994c), or somatostatin/ neuropeptide Y (NPY; Vincent et al, 1983;Chesselet and Graybiel, 1986;Vuillet et al, 1990;Kubota et al, 1993;Figueredo-Cardenas et al, 1996). In addition to these various types of GABAergic neurons, the caudate-putamen also receives GABAergic afferents from the globus pallidus (Staines et al, 1981;Staines and Fibiger, 1984;Kita and Kitai, 1991;Rajakumar et al, 1994).…”
mentioning
confidence: 97%
“…Projections coming from the cerebral cortex, the pars compacta of the substantia nigra and the thalamus are known to synapse both on projection neurons and interneurons (Kubota et al, 1987;Vuillet et al, 1990;Dimova et al, 1993;Bennett and Bolam, 1994;Kachidian et al, 1996Kachidian et al, , 1998Smith, 1996, 1999;Koó s and Tepper, 1999;Rudkin and Sadikot, 1999). Striatal inputs may influence the striatal output through directing their contacts onto striatal projection neurons or by exciting the interneurons which synchronize the discharge of several striatal projection neurons (Koó s and Tepper, 1999).…”
Section: Introductionmentioning
confidence: 99%